Tendentious Racism: A Critical Linguistics of the Humor Employed in Hasb e Haal Comedy Show - Abbasi, Talha Zahoor (ACADEMIA International Journal for Social Sciences, 2025)
Though making people laugh is humor's primary goal, it also has a big impact on how people feel about things. However, linguistic humor also entails the use of language to create or destroy persons identities. It is generally accepted that the purpose of humor is to make people laugh, amuse them and relieve tension.  In order to identify any hidden ideologies, the present study seeks uncover identity established by comedy in the program Hasb e Haal, which is shown on Pakistani news channel Dunya. As a qualitative case study, examples of verbal humor from several programs are evaluated using a critical linguistics framework. Data analysis shows that most of the time, people's physical characteristics, such as their fat and skin tone, are made fun of. The study reveals the inequality toward those who are deemed aesthetically unappealing to our cultural perception of beauty, addressing the affair of inequality addressed by Fairclough, 1995. Humor includes making fun of people based on their gender, ethnicity, and nationality in addition to their physical appearance. The essay concludes with some advice for TV networks in general and comedians, who, intentionally or unintentionally, act as agents of hatred and intolerance towards certain people and groups, reinforcing various forms of bigotry that also exist in our society.